Sistemas asociados de produccion frijol-maiz, frijol-papa, frijol-cana panelera, frijol-algodon, frijol-yuca, frijol-café - Tobón Cardona, JH (International Center for Tropical Agriculture, 1991)
Information is given of a subproject on bean-based intercropping systems in Colombia, Bolivia, Ecuador, and Peru as to responsible institutions and technicians, justification, duration, objectives, description of activities, and budget by country. (CIAT)